VETERINARY CARE BASED ON THE USE OF MEDICAL CANNABIS SPP. - Rosa, Ana Carla Rangel; Verly, Leonardo Bindelli; Gumiere, Tamiris da Silva; Costa, Gilvana de Oliveira; de Macêdo, Adriely Valerio; Andrade, João Victor; Perin, Isabelle Lucas Braga; Macedo, Maria Eduarda Dan; Dutra, Mariana Rodrigues Lugon; Marques, Cecília Fernandes Patta Muller; da Silva, Cibelle Ramos; Miranda, Giulia Stavrakas; et al. (Seven Editora, 2025)
Phytotherapy has been present in the daily life of humanity since the dawn of humanity, with several species of medicinal plants that are used for various purposes. However, phytotherapy aimed at veterinary medicine is still little explored, whose basis for treatments is often the transfer of knowledge applied to humans to animals. Plants of the Cannabis genus  are known for the richness of cannabinoid compounds, which for some years have been explored for their therapeutic and medicinal properties. The use of Cannabis in treatment for animals is an extremely recent subject, in view of the controversial public opinion about plants of this genus. However, studies have revealed specific receptors for cannabinoid compounds in various animal groups, from small invertebrates to large mammals, suggesting that the therapeutic use of Cannabis can be applied to veterinary treatments. The most striking compounds cited in studies focused on cannabis treatments  are Cannabidiol (CBD) and Tetrahydrocannabinol (THC), however more than 100 cannabinoid compounds are present that interact with brain receptors and can be explored in research, such as Cannabinol and Cannabigerol. Such receptors are found mainly in the central nervous system in vertebrates and are related to the regulation and maintenance of homeostasis. This chapter discusses the chemical composition, as well as the extraction and purification processes, interaction of cannabinoid compounds with endogenous CNS receptors and cannabis-based pharmaceutical formulations, seeking to contribute with a collection of current information on the use of this controversial plant in herbal treatments for veterinary use.DOI: https://doi.org/10.56238/sevened2024.037-122